How the West Was Lost: The Decline of Norse Settlements in Greenland - Johnathan Garceau 1995- (2025)
When the Norse arrived in Greenland they brought from Iceland their way of life, their farming methods and their worldviews. For nearly 500 years, they lived in two territories called the Western Settlement and the Eastern Settlement, which have been excavated since the early 1900s. Eventually, around the 15th century, the Norse settlements in Greenland would be abandoned. For a long time, the language used when talking of this historical event has been one of “collapse” and “demise.” Yet, all signs point to the Norse living in Greenland as they had years before in Iceland and Norway. Moreover, new research has put into question the deterministic views of earlier scholars who sought reasons behind the abandonment of the settlements in major causes such as climate and Inuit invasions. Based on the most recent archaeological and historical research, this thesis proposes that we should not talk of a societal collapse when speaking of the Norse in Greenland. Instead, the eventual abandonment was the cause of a slow trickle of events and factors like the inability of the Norse to create lasting and meaningful relationships with the Inuit’s who could have proved worthy allies in the difficult landscape of Greenland, their subsistence economy which even when changed did not answer all their needs, the climate which made travel more perilous and finally the economic isolation which was a result of changes in the demand for high-quality goods.